Techno economic evaluation of windmill for water pumping in coastal areas for aquaculture - Jayanthi, M; Ravishankar, T (Indian Journal of Fisheries, 2011)
Wind energy industry is relatively new, rapidly expanding and offers the potential to substantiate sufficient amount of power without causing pollution to the environment. With the Kyoto protocol aimed at reducing the greenhouse gas emissions across the globe, wind energy sector assumes greater importance as an alternative source of energy. An attempt has been made to develop a framework for techno-economic evaluation of windmills for water pumping. The discharge rate of windmill and its performance at 3m, 4m and 5 m heads were evaluated. The highest discharge was 175.68m3 / day at 23 Km/hr at 3m head and the lowest discharge rate was 51.49m3/day at 6km/hr at 5m head. The unit cost of water and energy delivered by the windmill were estimated. The monetary benefits that accrued to the end-user have been quantified in terms of the amount of diesel and electricity saved. The Net Present Value and Internal rate of returns for wter pumping using windmill, diesel pump and electric motor have been worked out to understand the efficiency of each sytem. The investment opportunities and support mechanisms were also highlighted